Electrochemical Sensing of Flutamide Contained in Plasma and Urine Matrices Using NiFe2O4/rGO Nanocomposite, as an Efficient and Selective Electrocatalyst. Issue 8 (17th April 2020) - Ensafi, Ali Asghar; Talkhooncheh, Bahareh Mandian; Zandi‐Atashbar, Navid; Rezaei, Behzad
Abstract: In this article, we report on the synthesis and new employment of magnetic nickelferrite oxide nanoparticles decorated reduced graphene oxide (NiFe2 O4 /rGO) to electrochemically sensing of flutamide. The preparation of this electrocatalyst was first assessed using various analytical instrumental techniques including FT‐IR spectroscopy, X‐ray diffraction spectroscopy, energy‐dispersive X‐ray spectroscopy, and field emission scanning and transmission electron microscopy. Besides, its electrochemical performance was investigated utilizing some electrochemical methods such as cyclic and differential pulse voltammetry, and also electrochemical impedance spectroscopy. The findings of this research are especially relevant for sensing flutamide in aqueous and biological samples. At the optimized conditions, the electrochemical sensor showed a linear range of 0.24–40.0 μmol L −1, the detection limit of 0.05 μmol L −1 flutamide, calibration sensitivity of 1.016 μA/μmol L −1, and repeatability and reproducibility of 1.7 % and 4.1 %, respectively. The selectivity of the method was investigated in the presence of ions, and species can generally exist in the biological medium. The resulting data of the present work represented that this type of magnetic nanocomposites is suitable for selective detection of flutamide in real samples of plasma and urine. The recoveries obtained for flutamide analyses represented lower than 5.0 percent of relative error in these real samples. Abstract :